Characterization of the complete plastid genome sequence of Magnolia buenaventurensis Á.J. Pérez & E. Rea (Magnoliaceae), a newly described species endemic to the Ecuadorian Andes - Edison Rea; Zhi-Qiong Mo; Álvaro J. Pérez; Hannah Mueller; Alex Harkess; Leslie R. Goertzen; Kevin S. Burgess (Mitochondrial DNA. Part B. Resources)
Magnolia buenaventurensis Á.J.Pérez & E.Rea 2023 is a newly described, endemic, and endangered species of the southwest Ecuadorian Andes mountains. Sequencing and characterizing its plastid genome will help clarify its relationship to other Neotropical Magnolia L. 1753. species. The plastid genome is 159,782 bp in length and includes 131 genes, 86 protein-coding genes (PCGs), 37 transfer RNAs (tRNA), and eight ribosomal RNA (rRNA) regions. Phylogenetic analysis confirms the species’ taxonomic classification in the section Talauma (Juss.) Baill 1866 and its close relationship to Magnolia gilbertoi (Lozano) Govaerts 1996 from Colombia, which belongs to the same section. However, the phylogenetic relationship shows low bootstrap support.